Cyclative Cascades of Allenamides Derived from Amino Acids: Synthesis of Annulated Indoxyl Derivatives. Issue 7 (19th February 2016) - Petkovic, Milos; Nasufovic, Veselin; Djukanovic, Dimitrije; Vujosevic, Zorana Tokic; Jadranin, Milka; Matovic, Radomir; Savic, Vladimir
Abstract: Allenamides derived from amino acids participate in the cascade transformations catalyzed by Pd 0 allowing consecutive formation of two five‐membered rings. The developed methodology provides an access to annulated indoles which can be transformed to functionalized indoxyl derivatives, retaining a structural motif embedded in several natural products. Abstract : Allenamides have been used as starting materials for the preparation of annulated indole derivatives. The reaction was initiated by the cyclization of the aryliodo moiety onto the proximal allene followed by intramolecular nucleophilic displacement involving the amino group. The obtained indoles were further transformed into indoxyl derivatives possessing structural features embedded in several natural products.